Aspek Hukum Izin Pinjam Pakai Kawasan Hutan dalam Kegiatan Pertambangan Mineral dan Batubara - Nadya Puspita Sari; Hamrin (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study examines the regulation of Forest Area Borrow-to-Use Permits (IPPKH) in mining activities, which have been transformed into Forest Area Use Approval (PPKH) following the enactment of Law Number 3 of 2020 and Law Number 6 of 2023. The objective of this research is to analyze the juridical framework of IPPKH/PPKH, identify issues related to overlapping permits, and formulate more effective and sustainable solutions. This study employs a normative juridical method with statutory, conceptual, and case approaches, analyzed qualitatively through library research. The results indicate that although the regulatory framework governing IPPKH/PPKH is relatively comprehensive, there are still inconsistencies among regulations, weak inter-agency coordination, and limitations in the implementation of the risk-based licensing system through Online Single Submission (OSS). Furthermore, overlapping permits are influenced by the lack of integrated spatial data and institutional capacity. This study concludes that regulatory harmonization, strengthened supervision, and optimized technological integration in the licensing system are necessary to achieve more effective forest area governance. These findings are significant as a basis for improving policies in sustainable natural resource management oriented toward public welfare.